|
|
Line 22: |
Line 22: |
| !Step 1: | | !Step 1: |
| |- | | |- |
− | |Use a ''u''-substitution with <math style="vertical-align: -8%">u = 3x + 2.</math> This means <math style="vertical-align: 0%">du = 3\,dx</math>, or <math style="vertical-align: -23%">dx=du/3</math>. After substitution we have | + | |Use a ''u''-substitution with <math style="vertical-align: -8%">u = 3x + 2.</math> This means <math style="vertical-align: 0%">du = 3\,dx</math>, or <math style="vertical-align: -21%">dx=du/3</math>. After substitution we have |
| ::<math>\int \left(3x + 2\right)^4 \,dx \,=\, \int u^4 \,\frac{du}{3}\,=\,\frac{1}{3}\int u^4\,du.</math> | | ::<math>\int \left(3x + 2\right)^4 \,dx \,=\, \int u^4 \,\frac{du}{3}\,=\,\frac{1}{3}\int u^4\,du.</math> |
| |} | | |} |
Latest revision as of 15:22, 15 May 2015
Find the antiderivative of
Foundations:
|
This problem requires three rules of integration. In particular, you need
|
Integration by substitution (u - sub): If is a differentiable functions whose range is in the domain of , then
|
|
We also need our power rule for integration:
|
- for .
|
Solution:
Step 1:
|
Use a u-substitution with This means , or . After substitution we have
|
Step 2:
|
We can no apply the power rule for integration:
|
Step 3:
|
Since our original function is a function of , we must substitute back into the result from step 2:
|
|
Step 4:
|
As will all indefinite integrals, don't forget the constant at the end.
|
Final Answer:
|
|
Return to Sample Exam